[Rezension von: Plutarch's Versatility] - Chrysanthu, Chrysanthos S. (The classical review, 2018)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0009840X18000100/resource/name/firstPage-S0009840X18000100a.jpg
Gesehen am 02.09.2019
Keywords: Rezension